Implementasi Program Kerjasama SMPN 50 kota Surabaya dengan Ikatan Pelajar Nahdatul Ulama Ikatan Pelajar Putri Nahdatul Ulama (IPNU-IPPNU) - Navyantito, Anggi; Megawati, Suci (Universitas Negeri Surabaya, 2024)
This research aims to analyze the implementation of the collaboration program between SMPN 50 Surabaya City and IPNU-IPPNU. The method used is descriptive qualitative with data collection techniques in the form of interviews, documentation and observation. The data sources used are the results of interview transcripts and observations, in the form of assessment of survey results, while the analysis technique uses descriptive qualitative. The research results indicate that the implementation of this collaborative program has been effective, supported by good coordination among the related elements, effective communication, and active student participation. This program has successfully instilled and strengthened the values of religious moderation and character education among students at SMPN 50 Kota Surabaya. This conclusion is expected to serve as a model for similar programs in other schools, with adjustments according to each context and need. Based on the results of the study, suggestions that can be given are: 1) improve the quality of communication between all parties involved in the IPNU-IPPNU cooperation program with SMPN 50 Surabaya; 2) Training and professional development for teachers, school staff, and IPNU-IPPNU members should be a priority; 3) Character building for all program implementers; 4) simplification of bureaucratic procedures, evaluation of the existing bureaucratic structure must be carried out to identify possible obstacles.